2013
DOI: 10.1002/14651858.cd004536.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional interventions for reducing morbidity and mortality in people with HIV

Abstract: Given the current evidence base, which is limited to fourteen relatively small trials all evaluating different macronutrient supplements in different populations at different stages of HIV infection and with varying treatment status, no firm conclusions can be drawn about the effects of macronutrient supplementation on morbidity and mortality in people living with HIV. It is, however, promising to see more studies being conducted in low-income countries, and particularly in children, where macronutrient supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
2
9

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 67 publications
4
92
2
9
Order By: Relevance
“…However, the treatment of adult malnutrition remains challenging, especially in resource-limited settings. In particular, interventions aimed at reducing mortality via direct replacement of presumed deficiencies, have yielded mostly negative results [54][55][56]. A recent Cochrane review of up to 14 trials found that in HIV-infected adults, neither supplementary whole food, nor provision of specific supplements such as protein or micronutrients reduced mortality [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the treatment of adult malnutrition remains challenging, especially in resource-limited settings. In particular, interventions aimed at reducing mortality via direct replacement of presumed deficiencies, have yielded mostly negative results [54][55][56]. A recent Cochrane review of up to 14 trials found that in HIV-infected adults, neither supplementary whole food, nor provision of specific supplements such as protein or micronutrients reduced mortality [54].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, interventions aimed at reducing mortality via direct replacement of presumed deficiencies, have yielded mostly negative results [54][55][56]. A recent Cochrane review of up to 14 trials found that in HIV-infected adults, neither supplementary whole food, nor provision of specific supplements such as protein or micronutrients reduced mortality [54]. Possible explanations for lack of effect from such interventions may include the targeting of wrong pathways, or failure to address more immediate causes of death or important co-existing disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent reviews on the effects of macronutrient supplementation (with or without nutritional counselling) on various clinical outcomes of people living with HIV offer inconclusive evidence of the positive impact on weight gain and CD4 count in developing countries [25,26]. Recent published studies that evaluated the impact of macronutrient supplementation to HIV infected individuals in resource-constrained setting include a quasi-experimental study in Zambia [27].…”
Section: Introductionmentioning
confidence: 99%
“…Aunque con la Terapia Antiretroviral de Gran Actividad (TARGA) han disminuido los casos de desnutrición y caquexia, persisten la disminución del apetito, ingesta alimentaria y pérdida de peso [1][2][3][4][5][6][7] . La dietoterapia forma parte del tratamiento integral de personas con infección por VIH, dado el riesgo de sufrir trastornos nutricionales y posibles efectos adversos de las medicaciones que pueden tener un impacto negativo en el estado nutricional e ingesta alimentaria [1][2][3][4][5][6][7] .…”
unclassified